2018
DOI: 10.1038/s41389-018-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A inhibits formation of homotypic cell-in-cell structures

Abstract: Cell-in-cell (CIC) structures, characterized by enclosure of one or more cells within another cell, were extensively documented in human cancers. Although elevated CIC formation was found in cancers with CDKN2A inactivation, a causal link between them remains to be established. We reported here that inhibiting CDKN2A expression effectively promoted homotypic CIC formation, whereas ectopic overexpression of p16INK4a or p14ARF, two proteins encoded by CDKN2A gene, significantly suppressed CIC formation in MCF7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…Indeed, CDKN2A status was found to be associated with various cancers [ 35 40 ]. A recent study identified CDKN2A as a tumor suppressor whose inactivation promoted homotypic cell-in-cell formation in human cancer cells [ 41 ]. Our analysis also suggested that CDKN2A might be a potential biomarker of recurrence in early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CDKN2A status was found to be associated with various cancers [ 35 40 ]. A recent study identified CDKN2A as a tumor suppressor whose inactivation promoted homotypic cell-in-cell formation in human cancer cells [ 41 ]. Our analysis also suggested that CDKN2A might be a potential biomarker of recurrence in early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Another tumour suppressor involved in entosis is CDKN2A . Inactivation of CDKN2A promoted entosis and CDKN2A expression and was inversely correlated to CIC formation in breast cancers [52]. Oncogenes have also been implicated in entosis and overexpression of KRAS V12 or c-Myc was shown to promote the formation of the CIC structures [15,53].…”
Section: The Relationship Between Cic Structures and Tumour Promotersmentioning
confidence: 99%
“…Several chemokines, cytokines and angiogenic factors produced by neutrophils may result in inflammatory cell recruitment and activation that crucially impact the tumor microenvironment, which could facilitate tumor cell proliferation, microvascular regeneration and tumor progression (9,14,15). The formation of CIC structure in tumors is a functional result of active intercellular interactions within heterogeneous tumor microenvironments, which is driven by a set of core molecular elements (16,17) that are regulated by multiple factors, such as cholesterol and IL-8 (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%